2007
DOI: 10.1364/oe.15.012905
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Nd:YAG LIBS emission of a remote target using a simultaneous CO_2 laser pulse

Abstract: For the first time to the best of our knowledge, a simultaneous 10.6 mum CO(2) laser pulse has been used to enhance the Laser Induced Breakdown Spectroscopy (LIBS) emission from a 1.064 mum Nd:YAG laser induced plasma on a hard target. The enhancement factor was on the order of 25 to 300 times, depending upon the emission lines observed. For an alumina ceramic substrate the Al emission lines at 308 nm and Fe impurity line at 278 nm showed an increase of 60x and 119x, respectively. The output energy of the Nd:Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Currently, there is much research being conducted on techniques to improve the sensitivity of LIBS or to increase the spectral intensity, to compensate for signal degradation over standoff differences [2,3]. One technique for doing so is dualpulse LIBS (DP-LIBS), where laser plasmas are reheated shortly after their formation with a second laser pulse [4]. Previous dual-pulse studies, which utilized Nd:YAG lasers and their harmonics for both plasma formation and reheating, showed a signal enhancement factor of 2-12× [4,5].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is much research being conducted on techniques to improve the sensitivity of LIBS or to increase the spectral intensity, to compensate for signal degradation over standoff differences [2,3]. One technique for doing so is dualpulse LIBS (DP-LIBS), where laser plasmas are reheated shortly after their formation with a second laser pulse [4]. Previous dual-pulse studies, which utilized Nd:YAG lasers and their harmonics for both plasma formation and reheating, showed a signal enhancement factor of 2-12× [4,5].…”
mentioning
confidence: 99%
“…One technique for doing so is dualpulse LIBS (DP-LIBS), where laser plasmas are reheated shortly after their formation with a second laser pulse [4]. Previous dual-pulse studies, which utilized Nd:YAG lasers and their harmonics for both plasma formation and reheating, showed a signal enhancement factor of 2-12× [4,5]. However, the reasons for the increased sensitivity have not been yet univocally ascertained, and a little effort has been made to understand the physics behind this emission enhancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been developed to improve the sensitivity of LIBS, such as, dualpulse excitation [8][9][10], spatial or magnetic confinement [11][12][13][14], microwave-assisted LIBS [15], and laser ablation combined with fast pulse discharge [16]. Generation of hightemperature and low-density plasmas in LIBS to improve the spectral resolution has also been achieved by introducing a second laser pulse to re-ablate the laser-induced particles with delays up to milliseconds [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we [30] studied the enhancement of optical emission plasmas confined with the combination of spatial and magnetic confinements, resulting in a maximum enhancement factor of only 24 for pure metallic Cr sample. Killinger et al [31] reported the enhancement of plasmas using a simultaneous CO 2 laser pulse, resulting in an increase of 60x for the Al atomic lines at 308 nm. In this study, our aim was to further improve the enhancement effects by the spatial confinement and dual-pulse in LIBS.…”
Section: Introductionmentioning
confidence: 99%